Perbedaan Kemandirian Berdasarkan Tipe Pola Asuh Orang Tua pada Siswa SMP Negeri di Denpasar - santosa, Ayu Winda Utami; Marheni, Adijanti (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2013)
In the developmental process, a child begins to form his personality through the family. The first environment that have most responsible on parenting children is the parents, then it has main influence on establishment of self-autonomy. The parenting style is one of the factor that frequently mentioned as cause for the development of self-autonomy. Every parent using different parenting style, therefore it will obtain different self-autonomy on every child also. The aim of this research is to investigate the difference of self-autonomy based on parenting style of the junior high school students in Denpasar. This research is a quantitative comparisons research. The subject of this research were 360 VII grade students of Junior High School in Denpasar. The sample were selected using proportionate stratified random sampling method. The data was collected through scales of parenting style that have been tested with reliability 0,886 and scales of self-autonomy that have been tested with reliability 0,876. Distribution of data obtained showed normal data and homogeneous data. Data obtained in this research is processed by comparisons of one way anova technique. Obtained results F = 9,998; p = 0.000 and Post Hoc analysis results showed that the Authoritative Parenting with Authoritarian Parenting have significance of 0.000, Authoritative Parenting and Permissive Parenting of 0,023, Permissive parenting with Authoritarian parenting of 0.002. The result indicate that there are significant differences between self-autonomy based on the type of Authoritative Parenting with Authoritarian Parenting, self-autonomy based on the type of Authoritative Parenting with Permissive parenting, and self-autonomy based on the type of Permissive Parenting and Authoritarian Parenting on Junior High School Students in Denpasar. Authoritative parenting is the type of parenting that obtain children with the best self autonomy. Keywords : parenting style, self-autonomy, junior high school students